The Effects of Upper Body Plyometric Training on Serving Skill of Female University Volleyball Players - Uzor, Theresa Nkiru; Iwuoha, Ekpereamaka Diamond; Ujuagu, Nonye Ann; Offodile, Humphery Nwanneka (S&Co Publishing, 2023)
This study examined the effect upper body plyometric on serving skills of female volleyball players. Two research questions guided the study. The study adopted a true experimental design, pre test posttest randomize control group. Out of twenty-two registered female volleyball players who voluntarily participated in the study, twenty female students were purposefully chosen from the university female volleyball team with body mass indices (BMI) between underweight and normal weight (≤14.5±18.9) (height, x=1.50±1.17cm; body weight, x=50.31±70.15kg). Only the volunteered final year female volleyball athletes were used for the study. No sample was used because the population is small. Data collected was analyzed using mean scores, standard deviation and t-test inferential statistics. The study revealed that upper body plyometrics training had an effect on the serving skill of female volleyball players. The study concluded that the serving skill of female university volleyball players will be greatly improved with the consistent use of plyometric training and recommended that coaches include lower and upper body plyometrics training in the training sessions and competitions for optimal performance.